Daily state of motivation as the effect of appreciation in a diary study - Seitl, Martin; Manuoglu, Elif; Hrbáčková, Anna (Current issues in personality psychology, 2024)
BACKGROUND: Grounded in self-determination theory, the present study aimed to investigate whether daily changes in employee motivation depend on whether employees receive appreciation from various sources at work, using a 7-day diary design. Beyond general knowledge about the effects of appreciation as an important source of motivation, there is still a lack of knowledge about the intrapersonal effect of appreciation on different types of regulation/motivation in terms of self-determination theory over time. PARTICIPANTS AND PROCEDURE: The sample consisted of 104 employees in full-time employment. More than half were women (72%) and the mean age was 43.25 years (SD = 10.53). They completed trait-level measures and then daily records, in which they reported their motivation and whether they received appreciation. Sources of appreciation were leaders, followers, and clients. RESULTS: Multilevel random coefficient modeling showed that employees reported higher levels of motivation on days when they received appreciation from different sources, independent of gender, trait-level motivation, and the Big Five. Furthermore, introjected regulation moderated the positive association between daily motivation and daily appreciation by the client, and appreciation did not have a lagged effect for subsequent days. CONCLUSIONS: The current study has both practical and theoretical implications. The results show that employee motivation can be supported through simple but effective steps through appreciation regardless of the source, although appreciation may be more important for employees with introjected regulation than for others.